Sadder but wiser: The Effects of Affective States and Weather on Ambiguity Attitudes - Aurélien Baillon; Philipp Koellinger; Theresa Treffers (Tinbergen Institute, 2014)
Many important decisions are made without precise information about the probabilities of the outcomes. In such situations, individual ambiguity attitudes influence decision making. The present study identifies affective states as a transient cause of ambiguity attitudes. We conducted two random-assignment, incentive-compatible laboratory experiments, varying subjects' affective states. We find that sadness induces choices that are closer to ambiguity-neutral attitudes compared with the joy, fear, and control groups, where decision makers deviate more from payoff-maximizing behaviors and are more susceptible to likelihood insensitivity. We also find a similar pattern in a representative population sample where cloudy weather conditions on the day of the survey - a proxy for sad affect - correlate with more ambiguity-neutral attitudes. Our results may help explain re al-world phenomena such as financial markets that react to regular fluctuations in weather conditions.
Keywords: D03; D81; 330; Ambiguity attitude; affect; joy; fear; sadness; weather; experiment.